CONTENT MARKETING : BRAND EXPERIENCE PRODUK FROZEN FOOD MELALUI CUSTOMER RETENTION - Fahimah, Mar'atul; Jan’nah, Hilda Nur Roudhotul (Universitas Wiralodra, 2023)
The Covid-19 pandemic encourages people to make lifestyle changes, including the food they eat. Due to the limited interaction, people will prefer to buy food that is easy to cook, durable, and nutritious. Frozen food or frozen food is the only right solution. The purpose of this study was to determine the effect of content marketing on brand experience through customer retention as an intervening variable for consumers of frozen food products on Instagram. The type of research used is associative. This study uses a purposive sampling technique and 100 respondents who are consumers who have followed and given likes to Cedea product posts. The results of this study indicate that content marketing has a significant effect on brand experience, content marketing has a significant effect on customer retention, customer retention has a significant effect on brand experience, and content marketing indirectly has a significant effect on brand experience through customer retention.